2014
DOI: 10.1002/jssc.201400329
|View full text |Cite
|
Sign up to set email alerts
|

A quick, easy, cheap, effective, rugged, and safe sample pretreatment and liquid chromatography with tandem mass spectrometry method for the simultaneous quantification of 33 mycotoxins inLentinula edodes

Abstract: Lentinula edodes, one of the most cultivated edible fungi in the world, are usually neglected for mycotoxins contamination due to the initial thinking of its resistance to mycotoxingenic molds. In the present study, a sensitive and reliable liquid chromatography with tandem mass spectrometry method was developed for the simultaneous quantification of 33 mycotoxins in L. edodes. Targeted mycotoxins were extracted using a quick, easy, cheap, effective, rugged, and safe procedure without any further clean-up step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The mycotoxins produced by various Fusarium strains were extracted and simultaneously determined by LC-MS/MS covering a total of thirty three frequently occurring mycotoxins, which has been established in the previous studies [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mycotoxins produced by various Fusarium strains were extracted and simultaneously determined by LC-MS/MS covering a total of thirty three frequently occurring mycotoxins, which has been established in the previous studies [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…F. oxysporum is a filamentous fungus isolated from the rizhosphere of S. spectabilis (Fabaceae) that produces several bioactive mycotoxins including trichothecenes, enniantins, and fumosinin. Among those, fusaric acid (5‐butylpyridine‐2‐carboxylic acid) is a polyketide and picolinic acid derivative abundantly produced under different growth conditions for this species, which displays a variety of bioactivity, including antifungal, antioomycete, antimicrobial, and herbicidal activities . Economically, this metabolite has been directly associated with Fusarium wilt, a trans‐boundary disease which affects different crops world‐wide, such as sugarcane, potatoes, bananas, and tomatoes, causing cracks in the tree stalk, leaf breakage, leaf yellowing, necrosis, and death, summing hundreds of millions of dollars in production losses …”
Section: Resultsmentioning
confidence: 99%
“…The results showed that within the wide-testing concentration range of each analyte, a good linear relationship existed, with coefficient of determination (R 2 ) between 0.9992 (AFG 1 and OTA) and 0.9997 (AFG 2 ). In general, nice and satisfactory sensitivities were obtained with LODs varying from 0.031 to 2.5 μg/kg and LOQs in the range of 0.078-6.25 μg/kg for all the seven analytes, which are obviously better than the sensitivities of the previously established methods for determination of multiple mycotoxins in Lentinula edodes, fish, seafood, and egg samples [40][41][42].…”
Section: Methods Validationmentioning
confidence: 99%